Strengthening the Economic and Social Resilience of the Cianjur Regency Community Due to the Impact of the Earthquake Disaster in Supporting National Security - Kurniadi, Anwar; `Syamsuniar, Syamsuniar; Widana, I Dewa Ketut Kerta (Technium Social Sciences Journal, 2023)
Strengthening economic resilience and social resilience will speed up the return to normal life due to the impact of the earthquake. For this reason, efforts need to be made to increase economic resilience and social resilience. This research aims to analyze efforts to strengthen economic resilience and social resilience carried out by the Cinajur district government and other stakeholders and their impact on national security. The research method uses qualitative with a case study design. The research subjects were 28 informants. After the data is collected, data analysis is carried out by condensing the data, presenting the data, and drawing conclusions. The results of the research show that strengthening economic resilience has been achieved well as demonstrated by the repair of 600 houses, roads and buildings have been rebuilt, People’s livelihoods are returning to normal so they can earn income; and social strengthening was achieved well, which was marked by government functions returning to normal, education running normally, people receiving free health insurance and the functioning of community groups returning to normal, Cianjur culture experienced a decline in the value of 2 of the 7 pillars but did not affect the interaction of people’s lives. The suggestion that can be made is for the regional government and community leaders, especially religious figures to raise awareness as a community that is experiencing the decline of Cianjur’s two cultures.